The effects of Nobiletin, Hesperetin, and Letrozole in a combination on the activity and expression of aromatase in breast cancer cells - Rahideh, S. T.; Keramatipour, M.; Nourbakhsh, M.; Koohdani, F.; Hoseini, M.; Shidfar, F. (Cellular and Molecular Biology, 2017)
Nobiletin (NOB) and hesperetin (HES) are the citrus polymethoxyflavone and flavonone. Aromatase or cytochrome P450 (CYP19) enzyme is a key enzyme in estrogen biosynthesis. The objective of this study was to investigate the combinational effects of HES, NOB and letrozole (LET) as aromatase inhibitors on the activity and expression of aromatase in MCF-7 cells. In this study, aromatase enzyme activity based on the conversion of androgen substrate testosterone to 17Î²-Estradiol was determined. Estradiol concentrations were measured using an electrochemiluminescence immunoassay. CYP19 gene expression was determined by quantitative real-time PCR. Our findings demonstrated that none of combinations including LET+NOB, LET+HES, LET+NOB+HES, and NOB+HES had no significant effects on aromatase activity and expression. The present study showed for the first time that the combination of HES, NOB, and LET had no effects on activity and expression of aromatase in MCF-7 breast cancer cells.